Indium oxide-based catalyst and its application in catalyzing the preparation of N-formyl compounds from DMF
By using a non-stoichiometric nano-indium oxide matrix-supported zinc single-atom catalyst to adjust the surface hydroxyl coverage of the catalyst and the interaction of the metal-carrier interface, the N-formylation reaction between DMF and amine compounds in the existing technology is solved. Problems that require strict anhydrous and oxygen-free conditions achieve efficient and economical catalytic effects in air atmosphere.
Patent Information
- Application Number
- CN202310434564.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-21
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-04-21
AI Technical Summary
In the prior art, when catalyzing the N-formylation reaction of DMF and amine compounds, strict anhydrous and anaerobic conditions are required, the reaction time is long, and additional additives or additives are required, which increases production costs and subsequent separation and purification. cost.
Using a non-stoichiometric nano-indium oxide matrix-supported zinc single-atom catalyst, by adjusting the surface hydroxyl coverage of the catalyst and the interaction of the metal-carrier interface, the N-formyl catalysis of DMF and amine compounds can be efficiently catalyzed in an air atmosphere. chemical reaction.
It achieves efficient catalysis without additional additives in air atmosphere, simplifies the operation process, reduces production costs, and improves reaction yield.
Smart Images

Figure CN116422318B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of chemical industry, and in particular to an indium oxide-based catalyst, a preparation method thereof and application thereof in catalyzing amines and DMF to prepare N-formyl compounds. Background Art
[0002] N,N-dimethylformamide (DMF) is a commonly used chemical reagent with low raw material cost and large industrial output. DMF is a safe, stable, cheap and easily available N-formylation reagent that meets the requirements of green and safe chemical processes and has important scientific research and industrial significance. Since the amide bond of DMF is very stable and chemically inert, the preparation of N-formylation products using the transamidation reaction of DMF usually needs to be carried out under strictly anhydrous and oxygen-free conditions, with a long reaction time and the need for additional auxiliary agents or additives. For example, in 2012, Mourabit et al. used boric acid (B(OH)3) as a metal-free catalyst for the transamidation reaction, DMF as a formylation reagent, and benzylamine (BnNH2) as a reactant, mixed with 1-2 equal amounts of water, and reacted at 140°C and 150°C for 20h, respectively, to obtain 67% and 83% N-benzylformamide. However, homogeneous catalysts increase the cost of subsequent separation and purification and are difficult to recycle. In 2015, Das et al. prepared a silica gel (H2SO4–SiO2) with sulfuric acid adsorption as a solid acid catalyst. DMF reacted with various aromatic amines at 70°C for 6-8h and was converted into the corresponding N-formylation products with good yields. However, the operation process of this reaction is quite harsh and needs to be carried out in a glove box. In addition, Ar gas protection is required during the reaction, which increases the production cost. Therefore, the development of new and efficient heterogeneous catalysts for the N-formylation reaction of DMF with amine compounds is an urgent problem to be solved.
[0003] In the prior Chinese invention patent application of the applicant of the present application, “A zinc single-atom catalyst, its preparation method and use in the catalytic preparation of N-formyl compounds” (application number: 202211425694.4), a zinc single-atom catalyst treated by a reducing atmosphere is described. Based on the research of the prior application, the inventors of the present application further discovered that a non-stoichiometric, cubic indium oxide carrier matrix treated with a non-reducing atmosphere, and the indium oxide matrix-loaded zinc single-atom catalyst (the metal-carrier interface has a metal-interface O-anchored coordination structure) and having a high hydroxyl coverage (40-60%) can catalyze DMF to form N-formyl compounds, thereby completing the present application. That is, the key preparation technologies of the catalysts in the previously applied patent (application number: 202211425694.4) and the present patent are different, resulting in different catalyst structural characteristics; in addition, the previously applied patent is applied to the preparation of N-formyl compounds using CO2 as a reactant, and the present patent is used to prepare N-formyl compounds using DMF as a reactant and does not require homogeneous catalysts such as phenylsilane, so the chemical reaction pathways and reaction mechanisms for preparing N-formyl compounds in the two patents are also different. It should be noted that the full text of the prior application is incorporated into the specification of the present application and serves as part of the specification of the present application. The applicant has the right to modify and / or state opinions on the application documents of the present application based on the contents recorded in the prior application. Summary of the invention
[0004] One of the problems solved by the present invention is to provide a catalytic synthesis technology for preparing N-formyl compounds, including using DMF to achieve N-formylation reaction of amine compounds, avoiding the use of N-formylation reagents such as acyl halides, acid anhydrides, formic acid, etc., which are high in cost, produce many by-products, and are highly corrosive to equipment, and to provide a new catalyst and its synthesis method. In order to solve the above technical problems, the present invention intends to adopt the following technical solutions:
[0005] The present invention relates to an oxide-based catalyst, which comprises a nano-indium oxide matrix, wherein the material ratio of In:O in the indium oxide is less than the stoichiometric ratio of 2:3, and the Fourier transform infrared spectrum of the catalyst is between 3000-4000cm -1 There are characteristic peaks between them, and the X-ray photoelectron spectroscopy test shows that the coverage of hydroxyl groups on the surface of indium oxide is 40-60% (preferably 40-50%), that is, it has a high coverage of hydroxyl groups; optionally, the nano indium oxide matrix is loaded with metal M, and the metal M is selected from one or more combinations of Zn, Co, Al, Ag, and Pd. The presence of the above characteristic peaks indicates that the catalyst of the present invention has abundant hydroxyl groups, thereby providing more sites for the adsorption and activation of reactant molecules, increasing the activity of the catalyst, accelerating the reaction process, and realizing multi-site synergistic catalysis of reactant molecules through the interaction between oxides and metals, thereby improving the reaction yield.
[0006] In a preferred embodiment of the present invention, the metal M is Zn.
[0007] In a preferred embodiment of the present invention, the matrix is cubic indium oxide.
[0008] In a preferred embodiment of the present invention, the matrix is porous flake-shaped indium oxide.
[0009] In a preferred embodiment of the present invention, the metal single atoms or nanoparticles loaded on the surface of the substrate are anchored by O atoms at the metal-support interface, that is, the interface between the metal M and the substrate has a MO coordination structure.
[0010] In a preferred embodiment of the present invention, the metal M is a single atom.
[0011] Another aspect of the present invention relates to a method for preparing the above catalyst, which comprises the following steps:
[0012] a. Disperse the indium-based metal salt and the organic weakly alkaline small molecule in the protic solvent respectively, add them into the protic solvent at a certain temperature in turn, heat and stir, cool naturally and then centrifuge and wash, and keep the precipitate in a vacuum drying oven for 8-12 hours;
[0013] b. calcining the precipitate obtained in step a at a high temperature, wherein the high temperature calcination is carried out in an air atmosphere at 200-550° C. for a calcination time of 1-6 hours to obtain a powdered sample;
[0014] c. Optionally, the powdered sample obtained in step b is dispersed in a reducing solvent, and a precursor salt solution of metal M is slowly added thereto. The mixture is stirred for a certain period of time, centrifuged for washing, and vacuum dried to obtain an oxide-supported metal catalyst.
[0015] In a preferred embodiment of the present invention, the indium-based metal salt in step a includes but is not limited to InCl3, In(NO3)3, In(acac)3, etc.
[0016] In a preferred embodiment of the present invention, the organic weakly basic small molecules in step a include but are not limited to hexamethylenetetramine (HMTA), triethanolamine (TEOA), tetrabutylammonium bromide, melamine, and the like.
[0017] In a preferred embodiment of the present invention, the precursor salt of the metallic zinc in step c includes but is not limited to ZnCl2, (CH3COO)2Zn, ZnSO4, Zn(NO3)2, Zn(acac)2 (zinc acetylacetonate), etc.
[0018] In a preferred embodiment of the present invention, the specific reaction conditions of step a are: 2-8 mmol of metal indium salt and organic weak alkaline small molecule are dispersed in 10-80 mL of protic solvent respectively, and then added to the protic solvent at 50-120° C. and heated at a constant temperature, stirred continuously for 1-4 hours, cooled naturally, and then washed and centrifuged and dried.
[0019] In a preferred embodiment of the present invention, the temperature of step b is 200-400° C. Within this preferred temperature range, the catalytic activity of the catalyst is improved.
[0020] In a preferred embodiment of the present invention, the specific reaction conditions of step c are: dispersing the powdered sample obtained in step b in a reducing solvent (including but not limited to CH3OH, C2H5OH), slowly adding 0.01-2M metal zinc salt precursor dispersion, stirring and immersing for 5-12 hours, then washing and centrifuging multiple times, and keeping warm in a vacuum drying oven for 8-12 hours.
[0021] Another object of the present invention is to provide an application of the above catalyst in catalytic preparation of N-formyl compounds, wherein the catalytic substrates are DMF and amine compounds. The catalyst prepared by the present invention can realize the high-efficiency catalysis of the N-formylation reaction of DMF on amine compounds in an air atmosphere without any additives. Compared with the prior art, the present invention has the advantages of simple operation and process, avoids the use of expensive acyl halides and acid anhydrides with more by-products and formic acid with equipment corrosion as formylation agents, is environmentally friendly, and reduces costs.
[0022] In a preferred embodiment of the present invention, the reaction temperature in the catalytic reaction is 100-180° C., the reaction pressure is normal pressure, the amount of the catalyst used is 1%-500% of the mass of the amine compound, and the reaction time is 8-24 hours.
[0023] In a preferred embodiment of the present invention, the amine compound used in the catalytic reaction is One or a combination of the following.
[0024] Beneficial results of the present invention: By optimizing the high-temperature calcination treatment method, the surface atomic structure and electronic structure of the nano-indium oxide matrix are adjusted, and a series of nano-In2O3 matrix structures with different hydroxyl sites are obtained to regulate the interaction between the carrier and the single-atom metal Zn. The study found that the Zn / In2O3-T200 with the highest surface hydroxyl content can efficiently catalyze the N-formylation reaction of DMF to aniline in an air atmosphere without the need for reaction conditions of dehydration and deoxygenation, and without the need for additional additives. The reaction operation and subsequent product collection and purification process are simple. In addition, through a series of characterization and control experiments, the study found that the composite catalyst of the nano-In2O3 matrix supporting Zn single atoms has a positive correlation between its surface hydroxyl content and catalytic performance. The indium oxide-based catalytic material of the present invention can achieve efficient catalysis of the N-formylation reaction of DMF to amine compounds under harsh reaction conditions such as air atmosphere (without the need for protective atmospheres such as O2, N2, Ar, etc.), without any additives, and without the need for water-free and oxygen-free reaction conditions. Avoid the use of N-formylation reagents such as acyl halides, acid anhydrides, and formic acid, which are high in cost, have many by-products, and are highly corrosive to equipment. This article proposes a new idea for regulating the interaction between oxides and metals, providing valuable experimental reference for the construction of efficient active sites of catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 : X-ray diffraction patterns of Zn / In2O3-T200 in Example 1, Zn / In2O3-T400 in Example 2, In2O3-T200 in Example 3, and Zn / In2O3-T600 in Comparative Example 1.
[0026] Figure 2 : Transmission electron microscopy image of the Zn / In2O3-T200 composite catalytic material in Example 1.
[0027] Figure 3 : Spherical aberration corrected high-resolution transmission electron microscopy image of the Zn / In2O3-T200 composite catalytic material in Example 1 and the atomic intensity distribution map of the corresponding area, with the single zinc atom marked in the circle.
[0028] Figure 4 : Transmission electron microscopy image of the Zn / In2O3-T400 composite catalytic material in Example 2.
[0029] Figure 5 : Transmission electron microscopy image of the Zn / In2O3-T600 composite catalytic material in Comparative Example 1.
[0030] Figure 6 : Spherical aberration corrected high-resolution transmission electron microscopy image of the Zn / In2O3-T600 composite catalytic material in Comparative Example 1 and the atomic intensity distribution map of the corresponding area, with zinc atoms marked in circles.
[0031] Figure 7 : Fourier transform infrared spectra of Zn / In2O3-T200 in Example 1, Zn / In2O3-T400 in Example 2, and Zn / In2O3-T600 in Comparative Example 1. At 602 cm -1 、565cm -1 、541cm -1 、434cm -1 The peaks on the left and right are characteristic absorption peaks of cubic In2O3. -1 The characteristic peak observed at 1622 cm -1 The small peak observed at can be attributed to the bending vibration of the surface hydroxyl groups. Based on the comparison, it can be concluded that the Zn / In2O3-T200 composite catalytic material with the lowest calcination temperature has a relatively higher hydroxyl content, and the content of surface hydroxyl groups varies with the change of calcination temperature.
[0032] Figure 8 : X-ray photoelectron spectra of the O1s orbital of the Zn / In2O3-T200 in Example 1, the Zn / In2O3-T400 in Example 2, and the Zn / In2O3-T600 in Comparative Example 1. The O peak at 529.8-530.1 eV can be attributed to the O atoms in In-O-In (i.e., the O lattice of In2O3), and the O vacancies on the surface of the In2O3 material are located at 531.2-531.8 eV (i.e., the O vacancies in the In2O3 lattice). V ), the peak position of O in the surface -OH (hydroxyl) is at 532.0-532.1eV (i.e., the hydroxyl O of In2O3). It can be clearly seen that there are differences in the content of -OH (hydroxyl oxygen) on the surface of these three materials, which is consistent with the results obtained by Fourier transform infrared spectroscopy. By integral area calculation, the hydroxyl content of Zn / In2O3-T200 in Example 1 accounts for 49% of In2O3, that is, it has a higher hydroxyl coverage, and the hydroxyl content of Zn / In2O3-T400 in Example 2 is slightly reduced to 46%; while the hydroxyl content of Zn / In2O3-T600 in Comparative Example 1 is only 3% of In2O3, which has a very low hydroxyl coverage. DETAILED DESCRIPTION
[0033] Example 1
[0034] a. Add 1-10 mmol InCl3 to 10 mL deionized water and 2-20 mmol HMTA as a precipitant, then add to 80 mL protic solvent preheated to a specified temperature and heat at a constant temperature, continue stirring and cool naturally, wash the precipitate several times, and then dry it.
[0035] b. Grind the dried solid thoroughly, heat it to 200-350°C in a muffle furnace and calcine it for 2-4 hours to obtain a non-stoichiometric indium oxide matrix precursor (non-stoichiometric ratio: the infrared spectrum shows the presence of hydroxyl groups in the material, and it also contains a small amount of lattice oxygen defects, and the actual material ratio of In:O is less than the stoichiometric ratio of 2:3), recorded as In2O3-T200;
[0036] c. Weigh 200-600 mg of the prepared In2O3-T200 and add an alcohol solvent to obtain a carrier dispersion, then prepare a 0.01-2 M ZnCl2 aqueous dispersion, and slowly inject it into the carrier dispersion under stirring, continue stirring and immersing, centrifuge and wash several times, and then dry to obtain the Zn-loaded oxide-based catalytic material Zn / In2O3-T200.
[0037] Example 2
[0038] a. Add 1-10 mmol InCl3 to 10 mL deionized water and 2-20 mmol HMTA as a precipitant, then add to 80 mL protic solvent preheated to a specified temperature and heat at a constant temperature, continue stirring and cool naturally, wash the precipitate several times, and then dry it.
[0039] b. The dried solid was fully ground, placed in a muffle furnace, heated to 400-550°C and calcined to obtain a non-stoichiometric indium oxide matrix precursor, denoted as In2O3-T400;
[0040] c. Weigh 200-600 mg of the prepared In2O3-T400 and add an alcohol solvent to obtain a carrier dispersion, then prepare a 0.01-2 M ZnCl2 dispersion, and slowly inject it into the carrier dispersion under stirring, continue stirring and immersing, centrifuge and wash several times, and then dry to obtain the Zn-loaded oxide-based catalytic material Zn / In2O3-T400.
[0041] Comparative Example 1
[0042] a. Add 1-10 mmol InCl3 to 10 mL deionized water and 2-20 mmol HMTA as a precipitant, then add to 80 mL protic solvent preheated to a specified temperature and heat at a constant temperature, continue stirring and cool naturally, wash the precipitate several times, and then dry it.
[0043] b. The dried solid was fully ground, placed in a muffle furnace, heated to 600-750°C and calcined for 2-4h to obtain a non-stoichiometric indium oxide matrix precursor, denoted as In2O3-T600;
[0044] c. Weigh 200-600 mg of the prepared In2O3-T600 and add an alcohol solvent to obtain a carrier dispersion, then prepare a 0.01-2 M ZnCl2 dispersion, and slowly inject it into the carrier dispersion under stirring, continue stirring and immersing, centrifuge and wash several times, and then dry to obtain the Zn-loaded oxide-based catalytic material Zn / In2O3-T600.
[0045] Example 3
[0046] a. Add 1-10 mmol InCl3 to 10 mL deionized water and 2-20 mmol HMTA as a precipitant, then add to 80 mL protic solvent preheated to a specified temperature and heat at a constant temperature, continue stirring and cool naturally, wash the precipitate several times, and then dry it.
[0047] b. The dried solid was fully ground, placed in a muffle furnace, heated to 200-350°C and calcined for 2-4h to obtain a non-stoichiometric indium oxide matrix precursor, denoted as In2O3-T200;
[0048] c. Weigh 200-600 mg of the prepared In2O3-T200 and add an alcohol solvent to obtain a carrier dispersion, prepare 0.01-2 M Co(NO3)2·6H2O aqueous dispersion, and slowly inject it into the carrier dispersion under stirring, continue stirring and immersing, centrifuge and wash several times, and then dry to obtain the Co-loaded oxide-based catalytic material Co / In2O3-T200.
[0049] Example 4
[0050] a. Add 1-10 mmol InCl3 to 10 mL deionized water and 2-20 mmol HMTA as a precipitant, then add to 80 mL protic solvent preheated to a specified temperature and heat at a constant temperature, continue stirring and cool naturally, wash the precipitate several times, and then dry it.
[0051] b. The dried solid was fully ground, placed in a muffle furnace, heated to 200-350°C and calcined for 2-4h to obtain a non-stoichiometric indium oxide matrix precursor, denoted as In2O3-T200;
[0052] c. Weigh 200-600 mg of the prepared In2O3-T200 and add an alcohol solvent to obtain a carrier dispersion, prepare 0.01-2 M Al(NO3)3 aqueous dispersion, and slowly inject it into the carrier dispersion under stirring, continue stirring and immersing, centrifuge and wash several times, and then dry to obtain the Al-loaded oxide-based catalytic material Al / In2O3-T200.
[0053] Example 5
[0054] 100 mg of Zn / In2O3-T200 catalyst in Example 1 was weighed and placed in a reaction tube. After ultrasonic dispersion, 1 mL of anhydrous DMF and 1 mmol of aniline were added thereto. Condensed water was connected and a balloon sealing system was connected to the condenser tube mouth. The reaction was placed in a heating jacket and stirred magnetically at a constant temperature of 160° C. for 10 h. After the reaction was completed, biphenyl internal standard was added thereto and centrifuged. The yield of N-phenylformamide was calculated by gas chromatography to be about 96%.
[0055] Example 6
[0056] 100 mg of the In2O3-T200 catalyst in Example 1 was weighed and placed in a reaction tube. After ultrasonic dispersion, 1 mL of anhydrous DMF and 1 mmol of aniline were added thereto. Condensed water was connected and a balloon sealing system was connected to the condenser tube mouth. The reaction was placed in a heating jacket and stirred magnetically at a constant temperature of 160° C. for 10 hours. After the reaction was completed, biphenyl internal standard was added thereto and centrifuged. The yield of N-phenylformamide was calculated by gas chromatography to be approximately 63.3%.
[0057] Example 7
[0058] 100 mg of Zn / In2O3-T400 catalyst in Example 2 was weighed and placed in a reaction tube. After ultrasonic dispersion, 1 mL of anhydrous DMF and 1 mmol of aniline were added thereto. Condensed water was connected and a balloon sealing system was connected to the condenser tube mouth. The mixture was placed in a heating jacket and stirred with magnetic stirring at a constant temperature of 160° C. for 10 h. After the reaction was completed, biphenyl internal standard was added thereto and centrifuged. The yield of N-phenylformamide was calculated to be about 74% using gas chromatography.
[0059] Comparative Example 2
[0060] 100 mg of Zn / In2O3-T600 catalyst in Comparative Example 1 was weighed and placed in a reaction tube. After ultrasonic dispersion, 1 mL of anhydrous DMF and 1 mmol of aniline were added thereto. Condensed water was connected and a balloon sealing system was connected to the condenser tube mouth. The mixture was placed in a heating jacket and stirred magnetically at a constant temperature of 160° C. for 10 h. After the reaction was completed, biphenyl internal standard was added thereto and centrifuged. The yield of N-phenylformamide was calculated to be about 27% using gas chromatography.
[0061] Example 8
[0062] 100 mg of the Co / In2O3-T200 catalyst in Example 3 was weighed and placed in a reaction tube. After ultrasonic dispersion, 1 mL of anhydrous DMF and 1 mmol of aniline were added thereto. Condensed water was connected and a balloon sealing system was connected to the condenser tube mouth. The mixture was placed in a heating jacket and stirred with magnetic stirring at a constant temperature of 160° C. for 10 h. After the reaction was completed, biphenyl internal standard was added thereto and centrifuged. The yield of N-phenylformamide was calculated by gas chromatography to be approximately 65.4%.
[0063] Example 9
[0064] 100 mg of the Al / In2O3-T200 catalyst in Example 4 was weighed and placed in a reaction tube. After ultrasonic dispersion, 1 mL of anhydrous DMF and 1 mmol of aniline were added thereto. Condensed water was connected and a balloon sealing system was connected to the condenser tube mouth. The mixture was placed in a heating jacket and stirred with magnetic stirring at a constant temperature of 160° C. for 10 h. After the reaction was completed, biphenyl internal standard was added thereto and centrifuged. The yield of N-phenylformamide was calculated to be about 65.1% using gas chromatography.
[0065] Comparative Example 3
[0066] a. Weigh 200-600 mg TiO2 and add alcohol solvent to obtain a carrier dispersion, then prepare 0.01-2 M ZnCl2 aqueous dispersion, and slowly inject it into the carrier dispersion under stirring, continue stirring and immersing, centrifuge and wash several times, and then dry to obtain the catalytic material Zn / TiO2.
[0067] b. Weigh 100 mg of Zn / TiO2 catalyst in Comparative Example 3 and place it in a reaction tube. After ultrasonic dispersion, add 1 mL of anhydrous DMF and 1 mmol of aniline, connect condensed water and connect a balloon sealing system to the condenser tube mouth, place it in a heating jacket and stir it with magnetic stirring at a constant temperature of 160°C for 10 hours. After the reaction, add biphenyl internal standard and centrifuge. The yield of N-phenylformamide is calculated by gas chromatography to be about 35.2%.
[0068] Comparative Example 4
[0069] a. Weigh 200-600 mg SiO2 and add alcohol solvent to obtain a carrier dispersion, then prepare 0.01-2 M ZnCl2 aqueous dispersion, and slowly inject it into the carrier dispersion under stirring, continue stirring and immersing, centrifuge and wash several times, and then dry to obtain the catalytic material Zn / SiO2.
[0070] b. Weigh 100 mg of Zn / SiO2 catalyst in Comparative Example 4 and place it in a reaction tube. After ultrasonic dispersion, add 1 mL of anhydrous DMF and 1 mmol of aniline, connect condensed water and connect a balloon sealing system to the condenser tube mouth, place it in a heating jacket and stir it with magnetic stirring at a constant temperature of 160°C for 10 hours. After the reaction, add biphenyl internal standard and centrifuge. The yield of N-phenylformamide is calculated by gas chromatography to be about 30.5%.
[0071] Example 10
[0072] 100mg Zn / In2O3-T200 catalyst in Example 1 was weighed and placed in a reaction tube. After ultrasonic dispersion, 1mL anhydrous DMF and 1mmol morpholine (or cyclohexylamine, p-methylaniline, p-chloroaniline and p-methoxyaniline) were added thereto. Condensed water was connected and a balloon sealing system was connected to the condensation tube mouth. The reaction was placed in a heating jacket and stirred at a constant temperature of 160°C for 10h. After the reaction was completed, trimethoxybenzene internal standard was added thereto and centrifuged. The yield of N-phenylformamide was calculated to be about 99.9% (97.5%, 91.2%, 76.4%, 73.0%) using nuclear magnetic resonance.
[0073] Typical embodiments of the present invention and typical examples of substrate expansion applicability are now compared and tabulated as follows, including but not limited to some different metal single atoms and carriers, as shown in Table 1.
[0074] Table 1
[0075]
[0076]
[0077] The above is only a description of the preferred embodiment of the present invention and does not impose any form of limitation on the present invention. Any improvement, modification and implementation based on the scheme or technology of the present invention without achieving creative results shall fall within the scope of protection of the technical scheme of the present invention.
Claims
1. An application of an oxide-based catalyst in catalytic preparation of N-formyl compounds, wherein the catalytic substrates are DMF and an amine compound, and the amine compound used in the catalytic reaction is The catalyst comprises a nano-indium oxide matrix, the material ratio of In:O in the indium oxide is less than the stoichiometric ratio of 2:3, and the Fourier transform infrared spectrum of the catalyst is between 3000-4000cm -1 There are characteristic peaks of hydroxyl groups, and X-ray photoelectron spectroscopy test shows that the coverage of hydroxyl groups on the surface of indium oxide is 40-60%; optionally, the nano indium oxide matrix is loaded with metal M, and the metal M is selected from one or more combinations of Zn, Co, Al, Ag, and Pd.
2. The use according to claim 1, wherein the metal M is Zn.
3. The use according to claim 1, wherein the matrix is cubic indium oxide.
4. The use according to claim 1, wherein the matrix is porous flake indium oxide.
5. The use according to claim 1, wherein the metal single atoms or nanoparticles loaded on the surface of the substrate are anchored by O atoms at the metal-support interface, that is, the interface between the metal M and the substrate has a MO coordination structure.
6. The use according to claim 1, wherein the metal M is a single atom.
7. The use according to any one of claims 1 to 6, wherein the method for preparing the catalyst comprises the following steps: a. Disperse the indium-based metal salt and the organic weakly alkaline small molecule in the protic solvent respectively, add them into the protic solvent at a certain temperature in turn, heat and stir, cool naturally and then centrifuge and wash, and keep the precipitate in a vacuum drying oven for 8-12 hours; b. calcining the precipitate obtained in step a at a high temperature, wherein the high temperature calcination is carried out in an air atmosphere at 200-550° C. for a calcination time of 1-6 hours to obtain a powdered sample; c. Optionally, the powdered sample obtained in step b is dispersed in a reducing solvent, and a precursor salt solution of metal M is slowly added thereto. The mixture is stirred for a certain period of time, centrifuged for washing, and vacuum dried to obtain an oxide-supported metal catalyst.
8. The use according to claim 7, wherein the metal precursor salt in step c is selected from ZnCl2, (CH3COO)2Zn, ZnSO 4、 Zn(NO3) 2、 One or more of Zn(acac)2 (zinc acetylacetonate).
9. The use according to claim 8, wherein the temperature in step b is 200-400°C.
Citation Information
Patent Citations
A zinc single atom catalyst, preparation method thereof and application in catalytic preparation of N-formyl compounds
CN115888683B
Zinc monatomic catalyst, preparation method thereof and application of zinc monatomic catalyst in catalytic preparation of N-formyl compound
CN115888683A